2015
DOI: 10.4049/jimmunol.1400923
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Thrombomodulin Inhibits Lipopolysaccharide-Induced Inflammatory Response by Blocking the Functions of CD14

Abstract: CD14, a multiligand pattern-recognition receptor, is involved in the activation of many TLRs. Thrombomodulin (TM), a type I transmembrane glycoprotein, originally was identified as an anticoagulant factor that activates protein C. Previously, we showed that the recombinant TM lectin-like domain binds to LPS and inhibits LPS-induced inflammation, but the function of the recombinant epidermal growth factor–like domain plus serine/threonine-rich domain of TM (rTMD23) in LPS-induced inflammation remains unknown. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 37 publications
(54 reference statements)
2
15
0
Order By: Relevance
“…Activated protein C not only works as an anticoagulant factor but also has indirect inflammatory activities . D‐2/3 also exhibits an anti‐inflammatory effect , and rTM has a protective effect in the murine liver resection model . In our study, pretreatment with rTMD1 demonstrated the suppression of sALT and serum HMGB‐1 levels in liver IRI to the same extent as rTM treatment.…”
Section: Discussionsupporting
confidence: 60%
“…Activated protein C not only works as an anticoagulant factor but also has indirect inflammatory activities . D‐2/3 also exhibits an anti‐inflammatory effect , and rTM has a protective effect in the murine liver resection model . In our study, pretreatment with rTMD1 demonstrated the suppression of sALT and serum HMGB‐1 levels in liver IRI to the same extent as rTM treatment.…”
Section: Discussionsupporting
confidence: 60%
“…Conversely, human leucocytes have been suggested to directly recognise the mucin-like region of thrombomodulin through leucocyte adhesion integrins lymphocyte function-associated antigen-1 (LFA-1) and Mac-1 in vitro [58]. Thrombomodulin EGF domains were found to markedly suppress LPS-induced inflammatory signalling pathways in macrophages by associating with the pattern recognition receptor CD14, and that this inhibitory effect was also dependent on the serine threoninerich domain [59]. Thrombomodulin EGF5 also has the capacity to engage T-cells bearing GPR15 [60].…”
Section: Thrombomodulin and Inflammationmentioning
confidence: 99%
“…Most importantly, monophosphorylated LPS derived from commensal or pathogenic bacteria triggers less CD14 activation, TLR4/MD-2 dimerization and endocytosis as compared to diphophorylated LPS [31]. The synergy between CD14 and thrombomodulin [32] or complement C5 [33] that leads to TLR4 activation and inflammatory responses also suggests that switching CD14 activation ON/OFF may be crucial to designing next generation adjuvants.…”
Section: Cd14 Activationmentioning
confidence: 99%